2018
DOI: 10.1159/000492556
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Competing Endogenous RNA Regulatory Networks in Vitamin A Deficiency-Induced Congenital Scoliosis by Transcriptome Sequencing Analysis

Abstract: Background/Aims: Congenital scoliosis (CS) is a result of anomalous development of vertebrae and is frequently associated with somitogenesis malformation. Although noncoding RNAs (ncRNAs) have been recently determined to be involved in the pathogenesis of CS, the competing endogenous RNA (ceRNA) regulatory networks in CS remain largely unknown. Methods: Sequencing was conducted to explore the ncRNA expression profiles in rat embryos (gestation day 9) following vitamin A deficiency (VAD) (n = 9 for the vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…Previous studies suggested that miRNAs play crucial roles in development, including stem cell differentiation, migration, metabolism, apoptosis and invasion . Our previous study also reported that miRNAs were deregulated in the development of VAD‐associated congenital spinal deformities . In this study, we selected one of the differentially expressed miRNAs, namely miR‐363, for further functional characterization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that miRNAs play crucial roles in development, including stem cell differentiation, migration, metabolism, apoptosis and invasion . Our previous study also reported that miRNAs were deregulated in the development of VAD‐associated congenital spinal deformities . In this study, we selected one of the differentially expressed miRNAs, namely miR‐363, for further functional characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital spinal deformity was induced by VAD in rats according to our previous study . Twenty female Wistar rats were randomly divided into the control group (n = 8) and VAD group (n = 12).…”
Section: Methodsmentioning
confidence: 99%
“…An accumulating number of studies have demonstrated that circRNAs play pivotal roles in cellular functions such as proliferation, differentiation, invasion, migration and metabolism, and their deregulation has been documented in different types of diseases, including cancers, neurodegeneration, inflammatory/immune diseases and orthopaedic conditions, such as scoliosis, osteoporosis and osteoarthritis . Recently, it has been reported that circRNAs are involved in the development of IDD .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, lncAIS impacts the function of NF90 and HOXD8 and hinders RUNX2 transcription . Previously, we performed sequencing data analysis to build ceRNA networks in embryonic tissues of rats with VAD‐induced CS and found that, based on Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, a SULT1C2A‐rno‐miR‐466c‐5p‐ Foxo4 axis as well as the Phosphoinositide 3 kinases (PI3K)‐AKT pathway appear to be involved in CS pathogenesis based on bioinformatics prediction and sequence analysis …”
Section: Introductionmentioning
confidence: 99%
“…18 Previously, we performed sequencing data analysis to build ceRNA networks in embryonic tissues of rats with VAD-induced CS and found that, based on Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, a SULT1C2A-rno-miR-466c-5p-Foxo4 axis as well as the Phosphoinositide 3 kinases (PI3K)-AKT pathway appear to be involved in CS pathogenesis based on bioinformatics prediction and sequence analysis. 19 In the present study, we aimed to confirm the expression of the lncRNA SULT1C2A in a rat model of VAD-induced CS and to explore the molecular mechanism of the SULT1C2A-rno-miR-466c-5p-Foxo4 axis in CS. This study of the effect of ceRNA dysregulation within the pathogenesis of VAD-CS provides insight into the mechanisms of somitogenesis and suggests that SULT1C2A may be a potential target for treating CS.…”
mentioning
confidence: 98%